Manual de coleta de amostras de sangue de cordão umbilical para realização de exames laboratoriais - Júnia Gonçalves de Almeida Quintão (2022)
Studies of blood from the umbilical cord have been conducted in recent decades with several objectives, such as assessing the length of clamping in the umbilical cord, the storage of stem cells, and collection for laboratory testing. Although uncommon, choosing blood from the umbilical cord for laboratory testing in the neonatal period permits rationing of available resources with reduced cost of care, increased speed of results, and reduced morbidity in the neonatal period. Our literature has yet to establish an instrument to guide the necessary blood collection from the umbilical cord by the professionals involved at the moment of birth. Childbirth care requires precision and speed from the entire team involved in direct care of the parturient and her baby. In this paper, we highlight the nursing staff present at birth, for in the investigated scenario such a stuff was selected by the unit managers to collect the blood samples from the umbilical cord for laboratory testing purposes. A methodological, descriptive, and quantitative research has been conducted on blood collection from the umbilical cord in newborns, with the objective of constructing a manual on the topic directed at the nursing staff. In order to add knowledge and describe each step involved in this process, we conducted an integrative literature review, which served as base for elaboration of the manual. In its validation stage, this manual was evaluated by experts in blood collection from the umbilical cord, guided by the Delphi method and by the nursing staff.The Likert ordinal scale was used in forms provided to both specialists and nursing staff.The Content Validity Index was used to assess the relevance and representativeness of its items by measuring the proportion or percentage of participants in agreement with the various aspects addressed in the manual. The sample consisted of 7 nurses trained in collecting blood from the umbilical cord for storage in stem cell banks, and 40 members of the nursing staff of the obstetric unit and the normal delivery center at the maternity ward targeted by the investigation. All agreed to participate willingly in the research through signing a Consent Form. This research was conducted according to the requirements of Resolution nº 466/2012 and approved by the Research Ethics Committee of the Federal University of Minas Gerais. The integrative literature review presented scientific evidence about the skills, competences and materials necessary for the nursing team’s collection of blood from the umbilical cord for laboratory testing of newborns. This low-cost strategy has great positive impacts on neonatal care, by utilizing an otherwise discarded placenta, with few risks for either mother or baby, and without causing the newborn any pain or discomfort. It was also clear that the success in collecting blood from the umbilical cord requires a team with the appropriate technical skills, with adequate work processes, and strategies of continuing and permanent education. The manual was formulated from robust and up to date scientific knowledge, and subsequently submitted for validation. In the process of content and presentation validation, experts considered each of the following topics for evaluation: objective; contente; language; illustrations; layout; motivation and culture. A mean Content Validity Index of 0.97 was reached. Experts valued most items as “Totally Adequate” or “Adequate”, and all pertinent recommendations were accepted, completing this process in the first round. The manual was also presented to the nursing staff of the investigated scenario for semantic analysis, in presential meetings. The topics evaluated were: objectives; organization; writing style; appearance and motivation. The agreement rate obtained was 99.9%, with suggestions to adapt some illustrations of the technical procedure to the content. These were analyzed and modified. Thus, this step of the validation process was also completed in its first round. The manual was formulated and validated as a technical product of this study, and it contains directions on collecting blood samples from the umbilical cord for laboratory testing in Neonatal Intensive Care Units. It consists of 27 pages, 11 chapters, 11 images, material checklist, flowchart and a six-item step-by-step guide. We conclude that it is possible to achieve the research objective with the construction of the collection manual, which can be used in Brazilian health units, aiding the qualification of professionals, the improvements of care processes, and hospital management.